2012
DOI: 10.1017/s0007114512004473
|View full text |Cite
|
Sign up to set email alerts
|

Iodine deficiency among Belgian pregnant women not fully corrected by iodine-containing multivitamins: a national cross-sectional survey

Abstract: Low iodine intake during pregnancy may cause thyroid dysfunction in pregnant women and their newborn. In the present study, iodine status among a nation-wide representative sample of Belgian pregnant women in the first and third trimester of pregnancy was determined, and determinants of iodine status were assessed 1 year after the introduction of bread fortified with iodised salt. The women were selected according to a multistage proportionate-to-size sampling design. Urine samples were collected and a general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 43 publications
8
29
1
4
Order By: Relevance
“…A comprehensive evaluation of the iodine status in pregnancy in Belgium has shown that median UI values are suboptimal [13]. This is despite the fact that 60% of the women reported taking iodine supplements during gestation [14]. Interestingly, the frequency of elevated neonatal thyroid-stimulating hormone levels was still low (3%) in this population [15].…”
Section: Tablementioning
confidence: 99%
“…A comprehensive evaluation of the iodine status in pregnancy in Belgium has shown that median UI values are suboptimal [13]. This is despite the fact that 60% of the women reported taking iodine supplements during gestation [14]. Interestingly, the frequency of elevated neonatal thyroid-stimulating hormone levels was still low (3%) in this population [15].…”
Section: Tablementioning
confidence: 99%
“…Фтор с меньшей атомной массой имеет пре-имущество при всасывании в кишечнике, вытесняя йод. Такую же позицию занимает и другой галоген-хлор при употреблении хлорированной воды как питьевой [11].…”
Section: таблица 3 заболеваемость детским туберкулёзом в иркутской обunclassified
“…Entretanto, se apresentar deficiência de iodo, este mecanismo adaptativo falha e pode levar à disfunção tireoidiana na mãe e no feto. (VANDEVIJVERE et al, 2012) Alguns estudos sugerem que a deficiência leve de iodo materno pode ter impacto no desenvolvimento neuropsicológico, psicomotor e intelectual completo de seus filhos (HADDOW et al, 1999; POP et al, 1999) O Fundo das Nações Unidas para a Infância (UNICEF) estima que, a cada ano, cerca de 38 milhões de recém-nascidos dos países em desenvolvimento continuam desprotegidos ao longo da vida das consequências do dano cerebral associado aos transtornos da deficiência de iodo. (FUSE et al, 2011) A ingestão adequada de iodo é o principal determinante do status nutricional desse mineral, mas a sua quantificação é difícil.…”
Section: Introductionunclassified
“…(VANDEVIJVERE et al, 2012). Existem poucos dados sobre o excesso de iodo durante a gestação e sua repercussão materno fetal.…”
Section: Introductionunclassified